MATCHING SKILLS TO CAREERS: THE IMPACT OF HUMAN CAPITAL ON JOB ALIGNMENT IN MALAYSIA - Low, Choon Wei; Mah, Pei Yew, (Malaysian Journal of Business and Economics (MJBE), 2024)
This study examines the impact of human capital factors on job-matching outcomes among Malaysian employees, emphasizing the roles of work experience and educational attainment. Utilizing a logistic regression model, the analysis reveals that both work experience and tertiary education significantly reduce the likelihood of job mismatches. The findings highlight the importance of employers offering adequate rewards, recognition, promotion opportunities, and work-life balance to enhance job satisfaction and retain employees. Additionally, the study underscores the critical role of tertiary education in preparing employees for the evolving demands of the Fourth Industrial Revolution (IR4.0). Despite its contributions, the study acknowledges a limitation in not capturing the specific educational programs studied by employees, suggesting this as a direction for future research.